Covalency-aided electrochemical CO2 reduction to CO on sulfide-derived Cu-Sb - Goh, Daniel Yong Yi (2024)
p-Block dopants like sulfur have been shown to break scaling relations in the electrocatalytic CO2 reduction reaction (CO2RR) by providing alternative binding sites with altered *CO binding energy. However, most sulfide-derived catalysts reported to date tend to produce formate or hydrogen during the CO2RR by shifting the reaction pathway away from C-bound intermediates. In this work, we discovered highly selective CO production on a bimetallic Cu-Sb-S derived catalyst. The high CO selectivity is in contrast with the individual control samples of CuSx and SbSx that demonstrate a preference towards the formate product. Interestingly, different starting phases and atomic ratios of Cu-Sb-S affect the CO2RR selectivity. Post-catalysis characterization coupled with DFT calculations indicates that the key enabler towards CO formation is the substitution of Sb sites with sulfur which improves *COOH binding relative to *CO, breaking scaling relations and facilitating subsequent CO (g) formation. The highest CO production of FECO = 80.5% was observed on the tetrahedrite Cu-Sb-S-derived sample at −1.0 V RHE with 37.6 mA cm−2 geometric partial current density.